2021
DOI: 10.1186/s12866-021-02186-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, population structure, distribution of serotypes, pilus islands and resistance genes among erythromycin-resistant colonizing and invasive Streptococcus agalactiae isolates recovered from pregnant and non-pregnant women in Isfahan, Iran

Abstract: Background The information on antibiotic resistance and molecular features of Group B Streptococcus (GBS) are essential for epidemiological purposes as well as vaccine development. Therefore, we aimed to assess the antimicrobial resistance profiles and molecular characteristics of GBS isolates in Isfahan, Iran. A total number of 72 colonizing and invasive GBS were collected from pregnant and non-pregnant women. The GBS isolates were analyzed for resistance profiles, capsular genotyping, and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
1
9
1
Order By: Relevance
“…The percentage of ermB in our study was very high compared to another study in Iran, where the gene was present at a low rate (29.3%) (Ghamari et al, 2022). Another study in Iran was (70%) (Motallebirad et al, 2021). ermB is one of erm genes that encoded Ribosomal modification, which is associated with (cMLSB)co-resistance to MLSB antibiotics with high-level resistance to all MLSB antibiotics (Ghamari et al, 2022).…”
Section: Molecular Detection Of Virulence Factors and Antibiotic Resi...contrasting
confidence: 48%
“…The percentage of ermB in our study was very high compared to another study in Iran, where the gene was present at a low rate (29.3%) (Ghamari et al, 2022). Another study in Iran was (70%) (Motallebirad et al, 2021). ermB is one of erm genes that encoded Ribosomal modification, which is associated with (cMLSB)co-resistance to MLSB antibiotics with high-level resistance to all MLSB antibiotics (Ghamari et al, 2022).…”
Section: Molecular Detection Of Virulence Factors and Antibiotic Resi...contrasting
confidence: 48%
“…The founders of CC12 and CC10, namely ST12 and ST10 respectively, were SLVs. Genetically, CC12 was derived from CC10 and flourished as a sub-clone in evolution ( Motallebirad et al, 2021 ). The genomes of CC12 and CC10 strains had more than 1700 orthologous clusters, but the genomes of CC12 were more unstable and variable because they had more mobile genetic elements.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance in GBS strains is a concern in the prevention of GBS invasive disease. The findings from recent studies support the increasing resistance to antibiotics used in GBS treatment [ 12 , 13 , 14 , 15 ], especially erythromycin and clindamycin, the second-line antibiotics recommended in cases of severe penicillin allergies, which have resistance rates of 21.3–74.1% in different regions [ 21 , 23 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The results of our study also demonstrated high resistance to erythromycin and clindamycin (40.0% and 21.4%, respectively).…”
Section: Discussionmentioning
confidence: 66%
“…For women allergic to penicillin with a history of severe reactions, the use of clindamycin or vancomycin is preferable [ 5 ]. However, recent studies have reported increasing antimicrobial resistance during GBS prevention [ 12 , 13 , 14 , 15 ]. Hayes et al reviewed antibiotic resistance in GBS prevention and reported that GBS is universally susceptible to beta-lactam antibiotics [ 14 ], whereas there have been reports of reduced susceptibility to beta-lactams, including penicillin, in some countries [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%